Perbandingan Ideologi Tokoh Pendidikan Jepang Zaman Edo Yoshida Shouin dengan Tokoh Yoshida Shouyou dalam Karya Sastra Gintama: Kajian Sosiologi Sastra - Noviandy, Dwiky; Rismorlita, Cut Erra; Hapsari, Eky Kusuma (NAWA: Journal of Japanese Studies, 2025)
This study aims to compare the educational ideologies of two figures: Yoshida Shouin, a historical figure from Japan’s Edo period, and Yoshida Shouyou, a fictional character from the anime Gintama. The research focuses on the ideologies and actions of both Yoshida Shouin and Yoshida Shouyou. The data are presented descriptively based on Sugiyono’s theoretical framework (2019) and further analyzed through the comparative lens of Winarno’s theory (as cited in Hasbi, 2013:6). The study concentrates on the field of education, as both Yoshida Shouin in historical context and Yoshida Shouyou in literary representation are depicted as influential educators to their students at Shouka Sonjuku. A qualitative descriptive method was employed, analyzing a total of 10 data points. The findings on Yoshida Shouin’s educational ideology reveal the following: essentialism (3 occurrences), conservatism (2), progressivism (3), and liberalism (2). Meanwhile, Yoshida Shouyou is characterized by the following ideological tendencies: essentialism (4 occurrences), conservatism (2), progressivism (2), and liberalism (2). Based on the analysis, it can be concluded that the two figures differ in terms of their foundational educational ideologies. Yoshida Shouin tends to align with essentialist and progressivist ideologies, whereas Yoshida Shouyou demonstrates a stronger inclination toward essentialist principles.